Pemilihan Supplier Bahan Baku Menggunakan Metode Analytical Hierarchy Process melalui Software Expert choice 11 di Toko Roti Queen Bakery Padalarang (Jurnal Riset Manajemen dan Akuntansi, 2025)
In the Micro, Small and Medium Enterprises (MSME) industry, the selection of suppliers of raw materials is an important aspect that affects product quality, operational  costs, and customer satisfaction. This research was conducted at Queen Bakery,  an MSME engaged in bread, to determine the best supplier of wheat  raw materials using the Analytical Hierarchy Process (AHP) method using the Expert choice 11 application. This research considers five main criteria, namely quality, price, delivery service, payment method, and  flexibility. Data were obtained through interviews and questionnaires filled out by  business owners and production division employees. The analysis results show that  quality criteria have the highest weight, followed by price and  delivery service. Based on the results of data processing, the best supplier selected is Toko Bapa Muslim (Supplier C) with the highest weight of 34.7% compared to other alternatives. The conclusion of this research is that the AHP  method is effective in helping Queen Bakery choose suppliers that are in accordance with  business needs and support the improvement of supply chain performance.